Analisis Perilaku Keuangan Mahasiswa Universitas Pelita Bangsa dalam Keputusan Investasi: (Analysis of Universitas Pelita Bangsa Student Financial Behavior in Investment Decisions) - Erin Soleha; Nani Hartati (LPPM Universitas Pelita Bangsa, 2021)
People with financial behavior that tend to be consumptive produce various bad things in financial behavior, for example the lack of saving and investing activities. Managing finances properly, planning and allocating a portion of income for investment is very important to provide benefits in the future. This study analyzes the effect of knowledge, financial attitudes, lifestyle, family background and the stage of the project using descriptive quantitative methods with data sources obtained from questionnaires distributed to 228 students who meet the criteria. Data analysis used descriptive statistical analysis, classical assumption test, multiple linear regression test with the help of the SPSS software program. The results of this study indicate that financial knowledge, financial attitudes, lifestyle, background and income have a positive effect on investment decisions.